Application Model Learning Scaffolding on the Subject Lesson Vocational Competence Student - Yosita, Lucy; Samawati, Anisa; Maknun, Johar (INVOTEC, 2016)
The background of this study is about the lack result and motivation of student in the Building Technique Class. Meanwhile the aims to determine the difference between the learning outcomes as well as motivation of students whose learning application of the learning model scaffolding to students who are learning to apply conventional learning models. This study uses a true experimental research methods by using posttest only control group design with quantitative approach. The subjects were students of class X Building Design Technique SMKN 9 Garut totaling 40 subjects involving teacher’s vocational competence. The research instrument is 5 essay tests to measure learning outcomes, 20 questionnaires to measure the motivation to learn and research documentation. Based on the analysis of research we concluded that: a) there is a difference between learning outcomes of students whose learning applying the learning model scaffolding with students who learning without applying the learning model scaffolding (conventional). This is indicated by the acquired Sig. amounting to 2.851 1.695 b) there is a difference between students' motivation is learning to apply learning models scaffolding with students whose learning without applying the learning model scaffolding (conventional). This is indicated by the acquired Sig. amounting to 2.851 1.685